2007
DOI: 10.1016/j.jalgebra.2006.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Families of Artinian and one-dimensional algebras

Abstract: The purpose of this paper is to study families of Artinian or one-dimensional quotients of a polynomial ring R with a special look to level algebras. Let GradAlg H (R) be the scheme parametrizing graded quotients of R with Hilbert function H . Let B → A be any graded surjection of quotients of R with Hilbert function H B = (1, h 1 , . . . , h j , . . .) and H A , respectively. If dim A = 0 (respectively dim A = depth A = 1) and A is a "truncation" of B in the sense that H A = (1, h 1 , . . . , h j −1 , α, 0, 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Recently J.O. Kleppe has shown that L (H) and LevAlg(H) give the same topological structures [Kle4,Theorem 44], extending his earlier result that there is an isomorphism between the tangent spaces to LevAlg(H) and to L(H) at corresponding closed points.…”
Section: Parametrization Of the Familymentioning
confidence: 62%
See 4 more Smart Citations
“…Recently J.O. Kleppe has shown that L (H) and LevAlg(H) give the same topological structures [Kle4,Theorem 44], extending his earlier result that there is an isomorphism between the tangent spaces to LevAlg(H) and to L(H) at corresponding closed points.…”
Section: Parametrization Of the Familymentioning
confidence: 62%
“…Kleppe has given an example where, proving a conjecture of the second author about the Hilbert function H = (1, 3, 6, 10, 14, 10, 6, 2), he shows that LevAlg(H) has at least two irreducible components. He also notes that by linking one can construct further such examples [Kle4,Example 49,Remark 50(b)]. …”
Section: Gorenstein Algebras and Level Algebrasmentioning
confidence: 99%
See 3 more Smart Citations